A study of smart mosque based on Internet of Things - Totonchi, Ahmed Talaat (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2020)
As of late, increasing enthusiasm for pervasive technology, for example, smart street lighting, service observing, smart city and the smart building has prompted expanded dependence on remotely sent IoT sensor devices for detecting and checking function. As of now, numerous devices have been conveyed worldwide, and a few more are being sent day by day. Smart buildings are expected that the advancement of Smart Mosque technology will redefine the manner in which we live later on in the future. The energy utilized in buildings cover a significant part of worldwide energy utilization. Indeed, even now, utilizing assured and economically accessible technology, it is potential to accomplish a significant decrease in building maintenance costs and energy utilization giving a progressively comfortable living environment simultaneously. Same like a lot of buildings, mosques handle numerous administration difficulties, for example, how to administer security, how to get the message out – for this situation, the word of Islam, and how to give the most satisfying experiences to mosque visitors. The main purpose of this study was to gather information on the Smart Mosque based on IoT. The primary objective of this thesis is to deal with the challenges within the current Mosques , and therefore the first objective that to identify the criteria of a Smart Mosque based on IoT and second research objective to identify the benefits of the Smart Mosque for Muslim ummah and Mankind. Moreover, the third objective to investigate the relationship between Smart Mosque and sustainable environment. Data were collected using online questionnaire and 141 responses were received. The finding of the first research objective showed that more than half of participants with 62.4% say that one of the main criteria of the Smart Mosque based on IoT can be automated building and another high rated participants with 36.2% that Smart Mosque should be environmentally friendless and another important criteria is Interact Smart Mosque with the energy system with 34%. The finding of the second research question shown that the majority of participants with 73% had answered that the Implementation of the Smart Mosque based on IoT would be benefits for Muslim ummah and Mankind because it is really need to adopt traditional mosque with modern technology nowadays. The finding of the third research questions shown that more than half of participants with 73.8% believe that Smart Mosque will be very effective and as mosque is one of the most important and widespread buildings in world and it will be very beneficial and play essential role in sustainable environment, and it is clear that sustainability, moderation, and cleanliness area unit entrenched in Muslim teachings and are integral to the faith of the believers.